Study on cohesion performance of waterborne epoxy resin emulsified asphalt as interlayer materials. (20th July 2018) - Liu, Mengmei; Han, Sen; Pan, Jun; Ren, Wanyan
Highlights: The cohesion of WEREA was investigated theoretically and experimentally. The curing agent A developed by the authors has good compatibility. Temperature and interlayer contact texture have significant effects on lateral cohesion. Abstract: Interlayer of pavement overlays or bridge deck pavement using waterborne epoxy resin emulsified asphalt (WEREA) is proposed for the purpose of preventing pavement from shoving at bridge deck. This study consists of theoretical analysis on cohesion and simulation failure tests of cohesion and waterproof. The results show that the cohesion performance is affected by temperature and the choice of curing agent, and the shear strength performance is related to interlayer contact texture. The components and network microstructure of WEREA enhance the cohesion property of interlayer and improve the material viscoelasticity, and as a result it improves the shear strength and pullout strength performance. In addition, WEREA also has a strong waterproof performance on the bridge deck pavement as tack coat.